MIDDLE SCHOOLS PSYCHOLOGICAL AND PEDAGOGICAL REQUIREMENTS FOR MULTIMEDIA ELECTRONIC LITERATURE CREATED FOR - J. A. Elmurodov (Academia Science Repository, 2023)
Psychological and pedagogical requirements for multimedia electronic educational literature created for secondary schools are presented.